Correlation of Steam Velocity and Pipe Diameter with Heat Transfer Performance on 120° Half-Pipe Jacket - Widarti, Sri; Rahayu, Irma Galuh; Prayogo, Sapto (Fluida, 2023)
Double jacket mixing tanks offer temperature control and versatility for industrial processes where temperature-sensitive materials need to be mixed, stored, or processed. The selection of the appropriate jacket type in a double-jacket mixing tank is based on the structural strength and the optimal heat transfer performance. The type of jackets can be conventional, dimple, and half-pipe. The conventional jacket is easier to manufacture, but it is not resistant to high temperature and pressure. The dimple jacket has good heat transfer, but it is susceptible to damage. The half-pipe jacket has good structural strength, but its heat transfer is affected by the central angle and pipe diameter. 120° central angle has greater heat transfer and pressure drop than 180° central angle. In order to determine the effects of steam velocity on heat transfer performance, heating time, and pressure drop of the 120° half-pipe jacket, research occurred on pipes with 2, 2.5, and 3 inches of diameter. The calculating method of heat transfer in agitated jacketed vessels is applied to visualize the relationships. The effects of steam velocity on heat transfer, heating duration, and pressure drop respectively are polynomials of order 2, power, and polynomials of order 2 with an average R2 close to 1. The greater R2, the better the relationship between two variables, according to the equation. The 120° half-pipe jacket performance will be highly effective, with 1774 W, 2.1 minutes heating duration, 8.94 kPa pressure drop if the steam velocity is 10.50 m/s with 2.5 inches pipe diameter.